Pengaruh Brand Image dan Harga Terhadap Keputusan Pembelian Produk Skincare di Subang - Dita Nur Syifa; Halimah Zahrah; Indra Sasangka (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Changes in consumer behavior encourage businesses to adjust their marketing strategies, with brand image and price becoming important factors in purchasing decisions. This study aims to determine the influence of brand image and price on consumer purchasing decisions at Toko Mega Berkah using a quantitative approach through surveys and multiple linear regression analysis. The results show that partially, brand image and price have no significant effect, but simultaneously, both have a significant effect on purchasing decisions. These findings indicate that purchasing decisions are influenced by a combination of brand image and price, so Toko Mega Berkah is advised to integrate brand image strategies with appropriate pricing.